The epidemiology of injury in english professional women`s football: a prospective cohort study - Mayhew, L.; Francis, P.; Jones, G. (British Journal of Sports Medicine, 2021)
Background Despite the professionalization of women`s football the incidence and prevalence of injuries occurring within England is currently unknown.